The accuracy of clinical symptoms in detecting cauda equina syndrome in patients undergoing acute MRI of the spine. Issue 4 (August 2015) - Ahad, Abdul; Elsayed, Mohammed; Tohid, Hassaan
A large number of patients do not have cauda equina syndrome (CES) on MRI to account for their clinical findings; consequently, the majority of urgent scans requested are normal. We aimed to determine whether any clinical manifestation of CES, as stated in Royal College of Radiology guidelines, could predict the presence of established CES on MRI. We also aimed to support a larger study to develop a more universal assessment tool for acute lower back pain. A retrospective analysis of consecutive patients who warranted urgent MRI was conducted. Seventy-nine patients were eligible for study. The Kendall's tau test was used for statistical analysis of all data. A p value of less than 0.05 was considered to be significant. MRI was performed in 62 patients out of 79. A total of 32.9% of patients had scans within 24 hours of admission. Nine of these patients were referred to neurosurgery for urgent neurosurgical review. Of these, 6.3% of patients had an established CES on MRI scan. One patient who had an out-patient MRI spine (15 days from hospital presentation) was found to have an established CES, was urgently referred to spinal surgery and underwent primary fenestration excision of the lumbar vertebra. No clinical features that were able to predict the presence of an established CES on MRI were elucidated. Findings included decreased anal tone 7.6% ( p = 0.282), faecal incontinence 3.8% ( p = 0.648), urinary retention 7.6% ( p = 0.510), bladder incontinence 8.9% ( p = 0.474), constipation 2.5% ( p = 0.011) and saddle anaesthesia 8.9% ( p = 0.368). Patients who had an abnormal MRI spine for back pain prior to this presentation showed a correlation with a newly diagnosed CES on MRI ( p = 0.016) with a correlation coefficient of 0.272.